Transglossic language practices of young adults in Bangladesh and Mongolia - Sultana, S.; Dovchin, Sender; Pennycook, A. (2015)
© 2014, Taylor & Francis. The paper explores the use of varied semiotic resources in the linguistic, social and cultural practices of young adults in the context of Bangladesh and Mongolia. Based on a translinguistic analysis (including pre-textual history, contextual relations, sub-textual meaning, intertextual echoes and post-textual interpretation) of these practices, and linking this to other recent calls to reconceptualise the notions of bilingualism and multilingualism, this paper combines Bakhtin's heteroglossic and Pennycook's transgressive approaches to the analysis of language practices through what we call a transglossic framework. The paper examines four sets of on/offline linguistic practices taken from two large ethnographic projects from Bangladesh and Mongolia and unravels the ways young adults recycle linguistic and cultural elements from popular culture and mobilise a range of semiotic resources for their communicative purposes. The paper finally suggests that a sophisticated theoretical construction of language as proposed by Bakhtin and Pennycook needs to be addressed and complemented with an equally advanced analytic tool, such as this transglossic framework.